Standardization of Saindhavadi Ghrita: A Herbal Ghrita for Computer Vision Syndrome - Vipul Shukla; B. Mukhopadhyay (International Journal of Ayurveda and Pharma Research, 2021)
Standardization is the present time need for acceptance of Ayurvedic polyherbal formulation. Standard polyherbal formulations have potency to check the pathogenesis of disease process without producing another disease. The upgrade the standard operating procedure can give new identity to the present era.An objective of the study is standardizing Saindhavadi Ghrita on various parameters, in order to assure its safety and efficacy on various basis. The Ghrita was analyzed for its organoleptic, physico-chemical features and screened for its phyto-constituents. In the present work, the obtained results were found within prescribed limits. The standard analytical methodologies provide safety and efficacy to the product, to avoid complication because eye is very sensitive and precious gift of god. So we cannot use Ghrita for Tarpan therapy without standardization.